1996
DOI: 10.1007/s002040050281
|View full text |Cite
|
Sign up to set email alerts
|

Sensory irritation mechanisms investigated from model compounds: trifluoroethanol, hexafluoroisopropanol and methyl hexafluoroisopropyl ether

Abstract: Quantitative structure-activity relationships (QSAR) have suggested the importance of hydrogen bonding in relation to activation of the sensory irritant receptor by nonreactive volatile organic chemicals. To investigate this possibility further, three model compounds with different hydrogen bond acidity, trifluoroethanol, hexafluoroisopropanol and methyl hexafluoroisopropyl ether, were selected for study. The potency of each chemical is obtained from the concentration necessary to reduce respiratory rate in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Esters can spontaneously participate in acyl-group transfer reactions (Nielsen 1991) or they can be hydrolyzed to acids (e.g. Plowchalk et al 1997) which then may activate the sensory irritant receptor (Nielsen 1991). The chemical reactivity of aldehydes is well known from organic chemistry.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Esters can spontaneously participate in acyl-group transfer reactions (Nielsen 1991) or they can be hydrolyzed to acids (e.g. Plowchalk et al 1997) which then may activate the sensory irritant receptor (Nielsen 1991). The chemical reactivity of aldehydes is well known from organic chemistry.…”
Section: Resultsmentioning
confidence: 99%
“…Using a database of 145 volatile organic chemicals inducing the same biological effect, i.e., sensory irritation, it has been demonstrated that the above rule, when used to divide the database into 56 non-reactive and 89 reactive (electrophiles) chemicals, can definitely be a good starting point (Alarie et al 1998) as originally proposed by Ferguson (1939). The same database was used to confirm earlier findings (Abraham et al 1990(Abraham et al & 1994Alarie et al 1995Alarie et al & 1996 that physicochemical descriptors can be used to estimate the sensory irritation potency of non-reactive chemicals, those having a P P ratio >0.1.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…(20) One of the first such processes to be studied was that of upper respiratory tract irritation in mice, the most recent and extensive equation [38] The 58 solutes used in Eq. (22) were all 'nonreactive' in that their irritancy effect is induced through essentially a physical mechanism [38][39][40].…”
Section: Glc Datamentioning
confidence: 99%